A Single-Center Retrospective Analysis of Local and Distant Relapse of Breast Cancer Following Immediate Breast Reconstruction According to Molecular Subtypes - Han, Chunyong; Zhang, Xuehui; Sun, Jingyan; Liu, Jing; He, Shanshan; Yin, Jian (Frontiers in Oncology, 2022)
Purpose Concerns have been raised about the oncologic safety of immediate breast reconstruction (IBR) following mastectomy for breast cancer. This study aimed to evaluate locoregional recurrence (LRR) and distant metastasis (DM) of breast cancer according to its molecular subtype in patients who underwent mastectomy alone or IBR after mastectomy. Methods In this retrospective cohort study, consecutive breast cancer patients treated by the single senior surgeon (XZ) between February 2010 and December 2014 were eligible. In total, 389 consecutive patients were included; 295 patients underwent mastectomy alone and 94 patients underwent mastectomy with IBR. Data were retrospectively collected and analyzed for LRR and DM stratified by molecular subtypes. Results With a median follow-up of 73 and 87.5 months, 1.69% of patients in the mastectomy alone group developed LRR compared to 0% in the reconstruction group (p = 0.342) and the total incidence of DMs was 11.52% in patients who received mastectomy alone and 7.44% in patients who received postmastectomy IBR (p = 0.262), respectively. The cumulative incidence of LRR was 2.1% vs. 0% for luminal A, 0% vs. 0% for luminal B, 0% vs. 0% for human epidermal growth factor receptor 2 (HER2)-enriched, and 4.5% vs. 0% for triple-negative in the mastectomy alone group compared to the postmastectomy IBR group. The cumulative incidence of DM was 15.5% vs. 5.7% for luminal A, 10% vs. 8.7% for luminal B, 17.3% vs. 0% for HER2-enriched, and 6.8% vs. 7.1% for triple-negative in the mastectomy alone group compared to the postmastectomy IBR group. On multivariable Cox regression analysis, lymph node metastasis was associated with an increased risk of DM in the mastectomy alone group (p = 0.03) and neoadjuvant chemotherapy was associated with an increased risk of DM in the postmastectomy IBR group (p = 0.021). Conclusion This study suggests that IBR does not have a negative impact on the LRR and DM of breast cancer according to molecular subtypes.